The social organization of Homo ergaster: Inferences from anti-predator responses in extant primates. Issue 109 (August 2017) - Willems, Erik P.; van Schaik, Carel P.
Abstract: Patterns of primate socioecology have been used to suggest that the first truly savanna-dwelling hominin, Homo ergaster, lived in sizeable groups. Here, we revisit these estimates and infer additional features of the social organization of these early hominins based on anti-predator responses observed across the primate taxon. We first show that the effect of habitat on primate group size, composition, and sexual dimorphism is negligible after controlling for substrate use and phylogeny: terrestrial species live in larger groups with more and bigger males than arboreal taxa. We next hypothesize that groups can only survive in open habitats if males are able to engage in joint counter-attacks against the large carnivorans typical of such environments. To test this, we analyze reports on primate counter-attacks against known predators and find these are indeed disproportionately frequent in terrestrial taxa living in open habitats, sometimes even involving the use of tentative weapons. If we subsequently only examine the taxa that are particularly adept at this (chimpanzees and baboons), we find an effect of habitat type on group size: groups on the savanna are larger than those in the forest. We thus infer that H. ergaster lived in very large groups with many males that jointly defended the group against carnivorans, and argue that these counter-attacks will readily have turned into confrontational scavenging and cooperative hunting, allowing Homo to move into the niche of social carnivore. These two features (life in very large multi-male groups and a switch to persistent carnivory) shaped the evolution of our lineage to such an extent that the social organization of H. ergaster may already have contained many key elements characterizing modern day foragers: male bonding, incipient male–female friendships with food sharing, a tendency toward endogamy, and the presence of large communities that eventually turned into the ethno-linguistic units we can still recognize today.